The Influence of Discipline and Competence on the Performance of Educational Personnel at PTIQ University with Job Satisfaction as a Mediating Variable - Dhia, Muhammad Rafi; Haryoto, Cecep Yoto (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The performance of educational personnel plays a vital role in achieving the goals of higher education institutions. However, work discipline and competence are often underutilized, which may affect job satisfaction and overall performance. This study offers a fresh perspective by examining the mediating role of job satisfaction in the relationship between work discipline, work competence, and employee performance within a faith-based university setting. A quantitative approach was applied, with data collected through questionnaires distributed to permanent educational staff. The analysis was conducted using Structural Equation Modeling with the Partial Least Squares method. The findings reveal that both work discipline and work competence have a positive influence on job satisfaction and performance. Moreover, job satisfaction enhances the indirect effects of discipline and competence on performance, confirming its role as a significant mediator. In conclusion, strengthening work discipline and competence—either directly or by improving job satisfaction—can serve as an effective strategy to boost the performance of educational personnel in higher education. These insights can guide institutional leaders and policymakers in designing more responsive human resource development programs tailored to the needs of academic support staff.